2015
DOI: 10.1021/acs.jproteome.5b00419
|View full text |Cite
|
Sign up to set email alerts
|

Network-Based Analysis on Orthogonal Separation of Human Plasma Uncovers Distinct High Density Lipoprotein Complexes

Abstract: High density lipoprotein (HDL) particles are blood-borne complexes whose plasma levels have been associated with protection from cardiovascular disease (CVD). Recent studies have demonstrated the existence of distinct HDL subspecies; however, these have been difficult to isolate and characterize biochemically. Here, we present the first report that employs a network-based approach to systematically infer HDL subspecies. Healthy human plasma was separated into 58 fractions using our previously published three o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
23
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 57 publications
1
23
0
Order By: Relevance
“…HDL's ability to carry out multiple atheroprotective functions may be explained by its compositional heterogeneity. Recent proteomic studies show HDL is highly compositionally heterogeneous, composed of particles, most all of which contain apoA-I, with related physico-chemical properties, but differ widely in their compositions and functions (12)(13)(14)(15)(16)(17). Additionally, correlational network analysis identified distinct protein clusters, which may represent specific HDL subspecies (15).…”
mentioning
confidence: 99%
“…HDL's ability to carry out multiple atheroprotective functions may be explained by its compositional heterogeneity. Recent proteomic studies show HDL is highly compositionally heterogeneous, composed of particles, most all of which contain apoA-I, with related physico-chemical properties, but differ widely in their compositions and functions (12)(13)(14)(15)(16)(17). Additionally, correlational network analysis identified distinct protein clusters, which may represent specific HDL subspecies (15).…”
mentioning
confidence: 99%
“…Although facilitation of reverse cholesterol transport through cholesterol acceptor activity is considered a major function of HDL particles, ample evidence shows additional functions exist, such as antioxidant, anti-inflammatory, and anti-tumorigenic activities, and the shuttling of microRNAs or lipid-signaling molecules (10 -16). HDL is a highly heterogeneous array of distinct particles, with differing associated proteome and peptidome (17)(18)(19)(20)(21)(22). In addition to exchangeable apolipoproteins, early proteomics studies revealed the HDL-associated proteome includes known participants critical to hemostasis and thrombosis, innate and adaptive immune function, growth factors and various receptors, and hormone-associated proteins (17,20).…”
mentioning
confidence: 99%
“…The health status and lipid profile of the study subjects also impact the composition of the HDL proteome, biological variables that are often evaluated in HDL proteomics studies. Nonetheless, despite all of the sources of variability listed above, approximately 90 proteins have persisted, and are thought to comprise the consensus HDL proteome [4]. We analyzed the consensus proteome using the Markov cluster algorithm (MCL) provided by the String data base (http://string-db.org/) that sorted HDL’s proteins into two major functional networks, one pertaining to lipid metabolism, and the other grouping several biological processes including protein activation cascades, regulation of wound response and regulation of protease activities (Fig.…”
Section: Unbiased Proteomics Applied To Hdl Biologymentioning
confidence: 99%
“…1a). Some of these studies have specifically addressed whether proteins are differentially localized across HDL size or density fractions [2, 4, 11, 12]. …”
Section: Unbiased Proteomics Applied To Hdl Biologymentioning
confidence: 99%